HUBUNGAN KARAKTERISTIK IBU DAN DUKUNGAN SUAMI TERHADAP PARTISIPASI IBU DALAM KELAS IBU HAMIL DI KELURAHAN HARJOSARI KECAMATAN TEBING KABUPATEN KARIMUN - Aisyah, Nur; Ibrahim, Ibrahim (Universitas Batam, 2019)
Maternal Mortality Rate (MMR) in Indonesia in fact is precisely still high compared to neighboring countries within Southeast Asia. Therefore, five main pillars are suggested as the strategies to reduce this MMR number namely family planning, qualifyAntenatal Care (ANC), delivery assistance by skilled health workers, emergency obstetric services, and postpartum services for mothers and babies. This study aims to dig out whether there is acorrelation between the characteristics of the mother and the husband support for the baby mother to join the antenatal class. This study employed analytical design of research with cross sectional approach conducted at Puskesmas Tebing in May 2018. The population of this study was all pregnant mothersregistered at Puskesmas Tebing with sample of 31 respondents derived using total sampling technique. The result shows mainly 58.1% respondents are in good childbearing age, the other 51.6% respondents have low educational background, besides 54.8% of them are mothers with multiparous parity. Furthermore,dominantly 71.0% respondents are working mothers, 67.7% of them get no support from their husband, thus,54.8% of the pregnant women in Puskesmas Tebing show less interest in joining the antenatal class. Theanalysis of Chi-Square testconfirms a correlation between each characteristic of mother’s age with p = 0.036 <0.05, mother’s education (p-value 0.001), mother’s participation (p-value 0.002), mother’s working status (p-value 0.008), therefore, it is correlated to the support of the expectant father with p = 0.001 <0.05. In conclusion, there is a significant correlation between mother’s characteristics and their husband’sencouragementfor joining the antenatal class for the preparation of baby delivery. Finally, it is suggested, in the real life contexts,the respondents to be able to apply information and knowledge as well as awarenessfrom this study.